2016
DOI: 10.1111/josh.12401
|View full text |Cite
|
Sign up to set email alerts
|

Policy Actions to Address Weight‐Based Bullying and Eating Disorders in Schools: Views of Teachers and School Administrators

Abstract: Educators recognize weight-related bullying and eating disorders as problems in their schools that warrant improved prevention and intervention efforts at the policy level.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
41
0
3

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 36 publications
(44 citation statements)
references
References 43 publications
0
41
0
3
Order By: Relevance
“…Future studies are needed to identify and evaluate community and school-based interventions to minimize WB and disordered eating. Research strongly supports the inclusion of content on prevention of eating disorders and WB in schoolbased curriculum (Aimé, LeBlanc, & Maïano, 2017;Puhl, Neumark-Sztainer, Austin, Suh, & Wakefield, 2016) and implementing school-based policies, with educators, school counselors, administrators, coaches, school nurses, parents, and students, to address weight bias (Puhl et al, 2016;Puhl, Neumark-Sztainer, Austin, Luedicke, & King, 2014) and disordered eating in schools (Neumark-Sztainer, Story, & Coller, 1999;Puhl et al, 2016;Yager & O'Dea, 2005).…”
Section: Resultsmentioning
confidence: 98%
“…Future studies are needed to identify and evaluate community and school-based interventions to minimize WB and disordered eating. Research strongly supports the inclusion of content on prevention of eating disorders and WB in schoolbased curriculum (Aimé, LeBlanc, & Maïano, 2017;Puhl, Neumark-Sztainer, Austin, Suh, & Wakefield, 2016) and implementing school-based policies, with educators, school counselors, administrators, coaches, school nurses, parents, and students, to address weight bias (Puhl et al, 2016;Puhl, Neumark-Sztainer, Austin, Luedicke, & King, 2014) and disordered eating in schools (Neumark-Sztainer, Story, & Coller, 1999;Puhl et al, 2016;Yager & O'Dea, 2005).…”
Section: Resultsmentioning
confidence: 98%
“…Participants were asked to indicate their perception of the impact on professional models of seven potential policy approaches, as well as their feasibility. The list of different policy approaches was developed by the authors after review the related literature and different policy proposals developed in the U.S. and abroad, and based on previous policy research methods (Puhl, Neumark‐Sztainer, Austin, Suh, & Wakefield, ; Puhl, Neumark‐Sztainer, Austin, Luedicke, & King, ). Feedback was solicited from a group of eating disorders experts at the Harvard T Chan School of Public Health.…”
Section: Methodsmentioning
confidence: 99%
“…In a survey of youth with overweight, over half (55%) reported that they would like teachers to intervene with instances of weight‐based bulling, and 44% reported the desire for PE teachers to intervene (Puhl, Peterson, & Luedicke, ). Educators report support for more training in bullying intervention as well (Puhl, Neumark‐Sztainer, et al., ). PE teachers in particular may benefit from training in this area, given that students are often bullied in PE class, and PE teachers report inconsistent responses to weight‐based bullying depending on student and teacher characteristics (such as gender; Peterson et al., ).…”
Section: Proposed Policies To Prevent and Reduce Weight Bias And Stigmamentioning
confidence: 99%
“…Despite the lack of weight-focused anti-bullying school policies, large-scale surveys of citizens in the United States, Canada, Iceland, and Australia suggest that public support for such programs is high across Western countries (Puhl, Latner, O'Brien, Luedicke, Forhan, et al, 2016). Stakeholders (persons with obesity, parents, and educators) also express strong support for school-based policies to prevent weightbased bullying (Puhl, Himmelstein, et al, 2017;Puhl, Neumark-Sztainer, Austin, Suh, & Wakefield, 2016;Puhl, Suh, et al, 2016). Additionally, public and parental support is strong for the use of litigation against schools that do not adequately intervene with weight-based bullying (Puhl, Luedicke, & King, 2015).…”
Section: School and Workplace Policiesmentioning
confidence: 99%